Divertor impurity seeding experiments at the COMPASS tokamak. (4th September 2019) - Komm, M.; Khodunov, I.; Cavalier, J.; Vondracek, P.; Henderson, S.; Seidl, J.; Horacek, J.; Naydenkova, D.; Adamek, J.; Bilkova, P.; Bohm, P.; Devitre, A.; et al.
Abstract: Partial detachment is the desired regime for the baseline burning plasma scenario in ITER and other next-step devices, as it allows for the dissipation of the majority of the energy carried by charged particles through the scrape-off-layer and thus avoids localised heat flux deposition in the divertor region. The COMPASS tokamak is equipped with an open divertor and has a relatively short connection length, both factors being unfavourable for access to detachment. As such, it only allows for the approach to naturally detached operation at very high line-averaged densities (>10 20 m −3 ), which are incompatible with maintaining the ELMy H-mode regime. In order to achieve detachment at lower densities, impurities (such as nitrogen) must be injected into the plasma in the divertor region. A series of experiments with impurity injection in the range of 1–9 10 20 molecules per second at different locations in the divertor were performed with the aim being to cool the plasma and influence particle and heat transport onto the divertor targets and provoke partial detachment. Previously reported results (Komm et al 2017 Proc. of the 44th EPS Conf . P1.118) were largely extended by injection of nitrogen at the outer divertor target. In order to analyze the divertor heat flux footprint in seeded plasmas, the buffered heat flux q B was introduced, with the radial profile being approximated by an exponential decay. A new set of generic parameters—the peak heat flux, the fraction of power reaching the target and divertor footprint spreading factor S f — were proposed to characterise the divertor footprint under detached conditions.